Extracellular Vesicles Derived From Human Umbilical Cord Mesenchymal Stem Cells Protect Against DOX-Induced Heart Failure Through the miR-100-5p/NOX4 Pathway - Zhong, Zhenglong; Tian, Yuqing; Luo, Xiaoming; Zou, Jianjie; Wu, Lin; Tian, Julong (Frontiers in Bioengineering and Biotechnology, 2021)
The end result of a variety of cardiovascular diseases is heart failure. Heart failure patients' morbidity and mortality rates are rising year after year. Extracellular vesicles (EVs) derived from human umbilical cord mesenchymal stem cells (HucMSC-EVs) have recently been discovered to be an alternative treatment for heart failure, according to recent research. In this study, we aimed to explore the underlying mechanisms which HucMSC-EVs inhibited doxorubicin (DOX)-induced heart failure in AC16 cells. A miR-100-5p inhibitor and a miR-100-5p mimic were used to transfect HucMSC using Lipofectamine 2000. HucMSC-EVs were isolated and purified with the ultracentrifugation method. AC16 cells were treated with DOX combined with HucMSC-EVs or EV miR-100-5-p inhibitor or EV miR-100-5-p mimic. ROS levels were measured by a flow cytometer. The levels of LDH, SOD and MDA were measured by biochemical methods. Apoptotic cells were assessed by a flow cytometer. Cleaved-caspase-3 and NOX4 protein expression was determined by Western blot. The experiment results showed that HucMSC-EVs inhibited DOX-induced increased levels of ROS, LDH and MDA, and decreased levels of SOD which were reversed by EV miR-100-5-p inhibitor. While EV miR-100-5-p mimic had a similar effect to HucMSC-EVs. At the same time, HucMSC-EVs inhibited DOX-induced the increases of apoptotic cells as well as NOX4 and Cleaved-caspase-3 protein expression, which were reversed by EV miR-100-5-p inhibitor. Furthermore, NOX4 expression was negatively regulated by miR-100-5p. Overexpression of NOX4 abolished the effects which HucMSC-EVs inhibited DOX-induced ROS, oxidative stress and apoptosis increases. In conclusion, these results indicate that HucMSC-EVs inhibit DOX-induced heart failure through miR-100-5p/NOX4 pathway.